High-strength and high-bending automobile doorsill beam aluminum alloy and preparation method thereof

By adjusting the Mg and Mn composition of aluminum alloy and optimizing the process flow, high-strength and high bending angle aluminum alloys are prepared, which solves the problem of insufficient strength and bending angle of existing aluminum alloys in automotive threshold beam applications, and realizes the Lightweight and cost-reduced effects while ensuring safety performance.

CN119506665APending Publication Date: 2025-02-25NINGBO XUSHENG AUTO TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411358977.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the application of automotive sill beams, existing aluminum alloys are difficult to meet the needs of high strength and high bending angles, especially the challenges of ensuring safety performance while reducing weight and cost.

Method used

By adjusting the composition ratio of Mg and Mn and optimizing the aging and quenching process, an aluminum alloy with Si 0.87-0.92%, Fe≤0.15%, Cu0.05-0.09%, Mn 0.58-0.63%, and Mg 0.88-0.93% was developed. , using air-slip casting, homogenization heat treatment, extrusion molding and fog + spray quenching, high-performance aluminum alloys with yield strength ≥280MPa, tensile strength ≥310MPa, and bending angle ≥75° were prepared.

Benefits of technology

It realizes the high strength, good bending angle and high elongation of aluminum alloy, meets the lightweight and safety performance requirements of automobile threshold beams, and reduces production costs, and the lightweight weight reduction effect can reach more than 20%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506665A_ABST
    Figure CN119506665A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength high-bending aluminum alloy and a preparation method thereof, the aluminum alloy comprises the following alloy elements in percentage by mass: 0.87-0.92% of Si, less than or equal to 0.15% of Fe, 0.05-0.09% of Cu, 0.58-0.63% of Mn, 0.88-0.93% of Mg, less than or equal to 0.10% of Zn, less than or equal to 0.10% of Ti, 0.08-0.12% of Cr, less than or equal to 0.05% of Zr, less than or equal to 0.05% of V and the balance of Al and inevitable impurities, the content of each impurity element is less than or equal to 0.05%, and the total amount of the impurities is less than or equal to 0.15%. The manufacturing method comprises the steps of alloy smelting, bar casting, homogenizing heat treatment, saw cutting, extrusion forming, aging treatment and the like. According to the aluminum alloy, the yield strength is larger than or equal to 280 MPa, the tensile strength is larger than or equal to 310 MPa, the bending angle can be kept at 75 degrees or above, the ductility is larger than or equal to 10%, and all key performance is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloys and manufacturing thereof, and in particular to a high-strength and high-bending aluminum alloy applicable to the technical requirements of lightweight automobile door sill beams and a preparation method thereof. Background Art

[0002] With the progress of society and the rapid development of technology, aluminum alloys are used more and more widely in production and life, and higher and higher requirements are placed on the performance of aluminum alloys, resulting in the inability of existing aluminum alloys to meet new demands.

[0003] Taking the automobile industry as an example, the transformation and upgrading of the automobile industry is gradually developing in the direction of new energy, lightweight, intelligent and networked. In particular, my country's new energy vehicles have developed rapidly in recent years, and production and sales have increased rapidly. Due to the many excellent properties of aluminum alloys, it has become a representative material for lightweighting automobiles, especially new energy vehicles. The application of lightweight aluminum alloy structural parts has played an increasingly important role in improving the performance and competitiveness of automobile products.

[0004] In recent years, with the gradual acceleration of the process of automobile lightweighting, the amount of aluminum used in domestic automobile structural parts and covering parts has begun to increase. According to preliminary statistics, in 2019, the average aluminum consumption of passenger cars in my country was 140 kilograms, which has increased year by year compared with previous years; among them, aluminum castings accounted for about 85%, and processed materials such as aluminum sheets, aluminum foils, aluminum extrusions and aluminum forgings accounted for about 15%. In particular, new energy vehicles have made great progress in automobile lightweighting, and the aluminum body rate of a few electric vehicles has reached more than 92%.

[0005] However, after the aluminum content of the vehicle body approaches or even reaches its limit, how to continue to achieve lightweighting of the vehicle has become an urgent problem to be solved. At the same time, the automotive industry has been under great pressure to reduce prices in the past two years, which requires that costs should be reduced as much as possible while lightweighting, but the vehicle's requirements for safety and other performance must also be met. Therefore, how to develop new aluminum alloys to meet the design requirements of lightweight vehicles and market price pressure has become an important task for the aluminum alloy industry.

[0006] 6 series aluminum alloys are widely used in automobiles, especially new energy vehicles, due to their light weight, good formability and easy welding. Take the automobile threshold beam as an example. At present, most power batteries are installed on the threshold beam. Therefore, the side collision of electric new energy vehicles may not only cause harm to the passengers in the car, but also may impact the power battery, causing battery explosion and other extreme safety accidents. Therefore, it is particularly important to develop a threshold beam aluminum alloy that is not only high in strength but also has a high bending angle and good energy absorption effect. To this end, the industry has also conducted a lot of research. For example:

[0007] Chinese invention patent application CN202310886856.2 discloses a 6-series aluminum alloy suitable for complex shape extrusion and its preparation method, the aluminum alloy, by weight percentage, the composition is 0.70-1.0% Si, 0.60-0.90% Mg, 0-0.40% Cu, 0-0.40% Fe, 0-0.20% Zr, 0-0.20% V, 0.01-0.10% Sr, 0.01%-0.05% Ti, Fe is the main impurity, the content of each other impurity does not exceed 0.05%, the total does not exceed 0.15%, and the rest is aluminum; Mg / Si is between 0.8 and 1.2, and Mg and Si correspond to the weight percentage content of Mg and Si. However, the tensile yield strength of the aluminum alloy is about 280MPa.

[0008] Chinese invention patent application CN 202211376430.4 discloses a method for preparing an aluminum alloy material for improving the crushing cracking level of a threshold beam, comprising the following steps: S1. Melting, wherein the aluminum liquid finally comprises the following components by mass percentage: Cu 0.05-0.2%, Mg 0.55-0.75%, Si0.7-0.9%, Mn 0.4-0.6%, Cr0.05-0.25%, Zn≤0.1%, Ti≤0.1%, Fe≤0.15%, and the remainder is Al; S2. Aluminum rod production; S3. Homogenization; S4. Sawing; S5. Extrusion; S6. Aging treatment; S7. Strength test; S8. Grain size detection; S9. Crush test verification. The application adjusts the magnesium-silicon ratio and increases the Mn content to ensure that the product has high performance while also having a high elongation. However, the tensile strength of aluminum alloy barely reaches 290MPa, and the yield strength is just over 260MPa.

[0009] Chinese invention patent 201911356780.2 discloses an aluminum alloy for automobile threshold beam and its preparation method, which comprises the following steps: (1) in the process of smelting aluminum liquid, adding aluminum-copper alloy, aluminum-silicon alloy, magnesium ingot and manganese agent; the mass percentage of the elements added in the final aluminum rod meets the following requirements: magnesium 0.90-1.10wt%, silicon 0.90-1.10%, manganese 0.50-0.80%, copper 0.20-0.40%; (2) filtering the aluminum liquid; (3) continuously casting through the casting system to cast aluminum rods; (4) transferring the aluminum rods into a homogenizing furnace for homogenization under the conditions of 550-570℃, 8-12H insulation, and wind and mist cooling; (5) sawing the aluminum rods to obtain short rods for extrusion. The alloy obtained in this patent has good strength, but its main purpose is to improve the performance after baking in different cycles. Its bending angle parameters are not disclosed, and it is impossible to judge whether it meets the safety requirements of the threshold beam.

[0010] Chinese invention patent application 202110630933.9 discloses an aluminum alloy for automobile threshold beams and a method for processing automobile threshold beams. The weight percentages of the components of the aluminum alloy in the application are: Si: 0.77-0.80%, Fe: ≤0.25%, Cu: 0.05-0.08%, Mn: 0.52-0.55%, Mg: 0.62-0.65%, Cr: 0.06-0.09%, Zn: ≤0.10%, Ti: ≤0.10%, and the balance is Al. The threshold beam processing method of the present invention adopts the aforementioned aluminum alloy. The aluminum alloy of the present invention has a tensile strength Rm ≥ 300MPa, a yield strength RP0.2 ≥ 270MPa, and an elongation A ≥ 12%.

[0011] However, under the trend of lightweighting in the automotive industry, aluminum alloys with the above performance indicators still cannot meet the needs of the automotive industry. Therefore, how to develop high-performance aluminum alloys that can meet the future lightweight requirements of the automotive industry threshold beams while meeting the composition requirements of the 6000 series has become an urgent task. Summary of the invention

[0012] The first technical problem to be solved by the present invention is to provide a 6 series aluminum alloy with high strength and large bending angle in view of the current status of the prior art, so as to meet the demand for door sill beams in the future automobile market.

[0013] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned aluminum alloy in view of the current status of the prior art.

[0014] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: the mass percentage content of each alloy element in the high-strength and high-bending aluminum alloy of the present invention is: Si 0.87-0.92%, Fe≤0.15%, Cu0.05-0.09%, Mn 0.58-0.63%, Mg 0.88-0.93%, Zn≤0.10%, Ti≤0.10%, Cr≤0.08-0.12%, Zr≤0.05%, V≤0.05%, the balance is Al and unavoidable impurities, the content of each impurity element does not exceed 0.05%, and the total amount of impurities does not exceed 0.15%.

[0015] The aluminum alloy has a yield strength of ≥280 MPa, a tensile strength of ≥310 MPa, and a bending angle of ≥75°.

[0016] The technical solution adopted by the present invention to solve the above second technical problem is: the preparation method of the high-strength and high-bend aluminum alloy of the present invention is characterized by comprising the following steps:

[0017] Alloy smelting: each required element or alloy of the elements is put into the smelting furnace in batches for melting. After the melting is complete, it is refined and degassed to obtain an aluminum alloy melt;

[0018] Rod casting: The obtained aluminum alloy melt is subjected to gas-slip casting to prepare aluminum alloy cast rods of target composition at a casting temperature of 680-720°C;

[0019] Homogenization heat treatment: homogenization heat treatment is performed on the obtained aluminum alloy casting rod;

[0020] Sawing: The homogenized bars are sawn to obtain short bars of preset length;

[0021] Extrusion molding: Use 4500T extruder to extrude the short rods, the extrusion process temperature is 510-530℃, and then quench online;

[0022] Aging treatment: The extruded profile is subjected to aging treatment at a temperature of 170 to 180°C and an aging time of 8.0 to 12.0 hours.

[0023] The homogenization heat treatment specifically comprises heating to 555-575° C. and maintaining the temperature for 9-11 hours, followed by air cooling.

[0024] The breakthrough pressure of the extrusion molding is 250-260 Bar, and the quenching is carried out by mist + spraying, the quenching temperature is 525-545°C, and the quenching temperature is ≤50°C.

[0025] The quenching parameters of the mist + spray method are total mist volume: total spray volume of 100:25-35.

[0026] Based on cost considerations, the inventors of this application hope to develop an aluminum alloy with a yield strength ≥ 280MPa, a tensile strength ≥ 310MPa, and a bending angle ≥ 75° based on the existing 6082 aluminum alloy during the research and development process. The overall research and development idea is: mainly to adjust the composition of Mg and Mn, with the aim of maintaining a relatively high and stable qualified mechanical value, and to determine the highest state that the bending angle can reach. Among them, the increase in Mg content is mainly to increase the strengthening precipitation phase, thereby improving the strength of the material. Appropriately increasing the Mn content can have the effect of refining the grains, which is beneficial to increasing the bending angle. At the same time, the aging process is optimized, especially the quenching process.

[0027] The study found that mist cooling quenching has a smaller effect on the deformation of the profile, while spray quenching has a greater effect on the deformation of the profile. Therefore, the present invention reduces a certain amount of spraying and applies additional mist cooling intensity, hoping to increase the quenching intensity while ensuring a smaller deformation. The existing conventional quenching is a total mist volume: total spray volume of 50:50, and after optimization, it is: total mist volume: total spray volume of 100:25-35.

[0028] Compared with the prior art, the advantages of the present invention are: the yield strength of the aluminum alloy of the present invention is ≥280MPa, the tensile strength is ≥310MPa, the bending angle can be maintained above 75°, and the elongation is ≥10%. The yield strength of the existing similar aluminum alloys is generally not higher than 280MPa, the tensile strength is not higher than 310MPa, and the bending angle is generally around 60°, while the key performances of the aluminum alloy of the present invention are significantly improved. Therefore, the aluminum alloy of the present invention has better lightweight characteristics, as well as stronger rigidity and toughness, which can ensure that the whole vehicle collision, head-on collision and offset collision reach a better level. The product can be used as a threshold beam in SUV new energy vehicles with higher requirements, while maintaining a good lightweight effect, and the lightweight weight reduction effect can reach more than 20%. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Illustration of the sampling location for the sill beam. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below with reference to the accompanying drawings.

[0031] 1. Trial production experiment series 1:

[0032] During the development of the present invention, the inventor team first conducted the following optimization research on the existing 6082 aluminum alloy, in order to achieve the purpose of the alloy of the present invention having a yield strength of ≥280MPa, a tensile strength of ≥310MPa, and a bending angle of ≥75°.

[0033] The optimized experimental 6082-01 aluminum alloy composition is: Si 0.912%, Fe 0.156%, Cu 0.0236%, Mn 0.521%, Mg 0.753%, Zn 0.0062%, Ti 0.02%, Cr 0.0982%, Zr 0.00051%, V0.017%, and the balance is Al and unavoidable impurities. The content of each impurity element does not exceed 0.05%, and the total amount of impurities does not exceed 0.15%.

[0034] The manufacturing process used is as follows:

[0035] Alloy smelting: each required element or alloy of the elements is put into the smelting furnace in batches for melting. After the melting is complete, it is refined and degassed to obtain an aluminum alloy melt;

[0036] Rod casting: The obtained aluminum alloy melt is subjected to gas-slip casting to prepare aluminum alloy cast rods of target composition at a casting temperature of 680-720°C;

[0037] Homogenization heat treatment: the obtained aluminum alloy casting rod is heated to 555-575℃ for 9-11h, and then air-cooled;

[0038] Sawing: The homogenized bars are sawn to obtain short bars of preset length;

[0039] Extrusion molding: Use 4500T extruder to extrude the short rods, the breakthrough pressure of extrusion molding is 250-260Bar, the extrusion process temperature is 510-530℃, and then use online mist + spray quenching, and the total mist volume: total spray volume is 100:25-35, the quenching temperature is 525-545℃, and the quenching temperature is ≤50℃;

[0040] Aging treatment: The extruded profile is subjected to aging treatment at an aging temperature of 175°C and an aging time of 8.0 h.

[0041] The properties of the aluminum alloy 6082-01 sill beam are shown in Tables 1 and 2.

[0042] Table 1 Test 6082-01 threshold beam aluminum alloy properties (the wall thickness unit is mm, the tensile strength and yield strength unit is MPa, the elongation is %, and the sampling position is shown in the table Figure 1 )

[0043]

[0044] Table 2 Test 6082-01 threshold beam aluminum alloy bending performance (the wall thickness unit in the table is mm, the bending angle unit is °, the sampling position is shown in Figure 1 )

[0045]

[0046] Note: The bending angle test method in the present invention adopts the standard VDA 238-100.

[0047] From the data in the table above, we can see that the strength and bending angle of some sampling points have not yet reached the expected target. Among them, the result of the mist + spray process performed best.

[0048] 2. Trial production experiment series 2:

[0049] After many experiments, it was found that the above alloy components could not achieve yield strength ≥ 280MPa, tensile strength ≥ 310MPa, and bending angle ≥ 75° after adjusting the production process parameters. The inventors conducted a series of formulation studies and adjusted the alloy components as follows:

[0050] The experimental 6082-03 aluminum alloy composition is: Si 0.879%, Fe 0.13%, Cu 0.0088%, Mn 0.541%, Mg 0.799%, Zn 0.0032%, Ti 0.0204%, Cr 0.102%, Zr 0.00034%, V 0.0125%, the balance is Al and unavoidable impurities, the content of each impurity element does not exceed 0.05%, and the total amount of impurities does not exceed 0.15%.

[0051] The experimental 6082-S aluminum alloy composition is: Si 0.893%, Fe 0.122%, Cu 0.0697%, Mn 0.611%, Mg 0.892%, Zn 0.0041%, Ti 0.0188%, Cr 0.0985%, Zr 0.0011%, V 0.012%, and the balance is Al and unavoidable impurities. The content of each impurity element does not exceed 0.05%, and the total amount of impurities does not exceed 0.15%.

[0052] The trial production process selected the mist + spray in test one, and the homogenization heat treatment was modified to raise the temperature to 555-575℃ and keep it for 9-11h, and then air cool.

[0053] Test 6082-03, 6082-S sill beam aluminum alloy properties are shown in Tables 3 and 4.

[0054] Table 3 Test 6082-03, 6082-S threshold beam aluminum alloy properties (the wall thickness unit is mm, the tensile strength and yield strength unit is MPa, the elongation is %, and the sampling position is shown in the table Figure 1 )

[0055]

[0056] Table 4 Test 6082-03, 6082-S threshold beam aluminum alloy bending performance (the wall thickness unit in the table is mm, the bending angle unit is °, the sampling position is shown in the table Figure 1 )

[0057]

[0058] From the above performance, it can be seen that after adjusting Mg and Mn, the mechanical value of the product tends to be stable but uneven, the yield value result is good, the tensile value is slightly worse in some positions, the elongation is lower in some positions, and the bending angle can reach about 65.

[0059] On this basis, the inventors studied the aging process, using 165℃*12h, 175℃*8h (original process), and 190℃*6h respectively.

[0060] The experiment found that, comparing the data of different aging systems, the comprehensive performance of the 165℃*12h product is improved compared with that of 175℃*8h, while the aging system is 190℃*6h, the tensile value and yield value are both reduced by about 10Mpa, the elongation is reduced by about 1%, and the bending angle has no obvious change, see trial test series three.

[0061] 3. Trial production experiment series 3:

[0062] The experimental 6082-S aluminum alloy composition is: Si 0.893%, Fe 0.122%, Cu 0.0697%, Mn 0.611%, Mg 0.892%, Zn 0.0041%, Ti 0.0188%, Cr 0.0985%, Zr 0.0011%, V 0.012%, and the balance is Al and unavoidable impurities. The content of each impurity element does not exceed 0.05%, and the total amount of impurities does not exceed 0.15%.

[0063] The trial production processes were 165℃*12h, 175℃*8h (original process), and 190℃*6h for aging. Other processes were the same as series 2.

[0064] The performance test data of different aging processes are shown in Table 5.

[0065] Table 5 Test threshold beam aluminum alloy properties (the wall thickness unit is mm, the tensile strength and yield strength unit is MPa, the elongation is %, and the sampling position is shown in the table) Figure 1 )

[0066]

[0067] Table 6 Test of bending properties of aluminum alloy threshold beams with different aging processes (the wall thickness unit in the table is mm, the bending angle unit is °, and the sampling position is shown in the table) Figure 1 )

[0068]

[0069] The above test results show that the performance of the alloy obtained by aging at 165℃*12h has fully reached the target.

[0070] 4. Based on the above experiments, the inventors conducted a series of research on the formulations. The corresponding alloy compositions are shown in Table 7. The trial production process is the same as that of Series 3 except for the aging process, which uses 165℃*12h or 170℃*11h.

[0071] Table 7

[0072]

[0073] Table 7 Aluminum alloy product performance data see Table 8

[0074] Table 8 (Note: The product performance data in this table are selected from the worst data of each sampling point of each sample. The wall thickness unit in the table is mm, the tensile strength and yield strength unit is MPa, the elongation is %, the bending angle unit is °, and the sampling position reference Figure 1 . )

[0075] Alloy grade tensile strength Yield Strength Elongation Bending Angle 6082-S-1 311.99 283.01 14 80.12 6082-S-2 318.36 287.66 12 75.36 6082-S-3 316.21 285.47 12.5 77.42 6082-S-4 321.56 289.57 13 76.55 6082-S-5 313.97 286.09 12.5 76.37 6082-S-6 316.82 285.39 12 78.48

Claims

1. A high-strength and high-bending aluminum alloy, characterized in that The mass percentage of each alloying element in the aluminum alloy is: Si 0.87-0.92%, Fe≤0.15%, Cu 0.05-0.09%, Mn 0.58-0.63%, Mg 0.88-0.93%, Zn≤0.10%, Ti≤0.10%, Cr 0.08-0.12%, Zr≤0.05%, V≤0.05%, the balance is Al and unavoidable impurities, the content of each impurity element does not exceed 0.05%, and the total amount of impurities does not exceed 0.15%.

2. The high-strength and high-bend aluminum alloy according to claim 1, characterized in that The aluminum alloy has a yield strength of ≥280 MPa, a tensile strength of ≥310 MPa, and a bending angle of ≥75°.

3. A method for preparing the high-strength and high-bend aluminum alloy as claimed in claim 1, characterized in that: The steps include: Alloy smelting: each required element or alloy of the elements is put into the smelting furnace in batches for melting. After the melting is complete, it is refined and degassed to obtain an aluminum alloy melt; Rod casting: The obtained aluminum alloy melt is subjected to gas-slip casting to prepare aluminum alloy cast rods of target composition at a casting temperature of 680-720°C; Homogenization heat treatment: homogenization heat treatment is performed on the obtained aluminum alloy casting rod; Sawing: The homogenized bars are sawn to obtain short bars of preset length; Extrusion molding: Use 4500T extruder to extrude the short rods, the extrusion process temperature is 510-530℃, and then quench online; Aging treatment: The extruded profile is subjected to aging treatment at a temperature of 165 to 170°C and an aging time of 11.0 to 12.0 hours.

4. The preparation method according to claim 3, characterized in that: The homogenization heat treatment specifically comprises heating to 555-575° C., maintaining the temperature for 9-11 hours, and then air cooling.

5. The preparation method according to claim 3, characterized in that: The breakthrough pressure of the extrusion molding is 250-260 MPa, and the quenching is carried out by mist + spraying, the quenching temperature is 525-545°C, and the quenching temperature is ≤50°C.

6. The preparation method according to claim 5, characterized in that: The quenching parameters of the mist + spray method are total mist volume: total spray volume of 100:25-35.

Citation Information

Patent Citations

  • An aluminum alloy for automobile door sill beams and its preparation method

    CN111074087B

  • Aluminum alloy for automobile doorsill beam, and machining method of automobile doorsill beam

    CN113528898A

  • Preparation method of aluminum alloy material for improving crushing cracking grade of doorsill beam

    CN115807173A

  • 6-series aluminum alloy suitable for complex shape extrusion and preparation method of 6-series aluminum alloy

    CN116987935A